The United States and Latin America - The American Assembly; MAtthews, Herbert Lionel, 1900- (Englewood Cliffs, NJ : Prentice-Hall, 1963)
A Spectrum book
Keywords: Latin America -- Civilization; Latin America -- Relations (general) with the U.S.; U.S. Relations (general) with Latin America